The end of humanism as the locus of Pirjevec's thinking - Komel, Dean (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In his reflection upon the crisis of humanism, the Slovenian literary theorist and philosopher Dušan Pirjevec proceeds from the critique of the humanistic orientation as represented by poststructuralist philosophers in the 1960s, but treats the problem of the “end of humanism” in a much more complex light of nihilism of the epoch of the world. At the same time, direct existential experience from the Second World War as well as with the totalitarian ideologies that marked the 20th century was of crucial importance for his understanding of the problem of humanism. Pirjevec developed his key philosophical insights mainly in his studies on the European novel ranging from Cervantes to Robbe-Grillet, following the basic existential orientation that it is necessary, before any (revolutionary) attempt to assert the ideas of “new humanity,” to recognize the human ethos.